Javanese Religious Expression Through Kenduren Tradition - Fifi Nur Rokhmah (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
This research aimed to analyze Javanese religious expression which was realized in a form of kenduren tradition. The researcher used semiotics approach to interpret the symbols in kenduren tradition and expose integrative Islamic education in the tradition. The conclusion of the research was kenduren as one of the religious expressions for Javanese people. Through the tradition, the society integrated several Islamic teachings such as prayer, zikir, gratitude expression, silaturahim (maintain human relationship), and human equality. Therefore, the people involved in kenduren was expected to have a better attitude because they have implemented the value of Islamic teachings through the tradition.